Verrucous lymphangioma circumscriptum. - Milano, A. (European Journal of Pediatric Dermatology, 2019)
Lymphangioma circumscriptum (LC) is a superficial lymphatic malformation more frequent than deep forms such as cavernous lymphangioma and cystic hygroma. However, LC can be associated and communicate with a deep lymphangioma. LC forms during embryogenesis due to a segregation of lymphatic vessels that lose connection with the physiological lymphatic system (2). The frequent presence of blood in the vesicles could be due to a concomitant venous malformation or more simply to post-traumatic bleeding. The literature speaks of verrucous lymphangioma circumscriptum as a particular form of LC that poses important problems of differential diagnosis with other disorders, from common wart to tuberculosis (1). The current case demonstrates that verrucous LC may be the normal evolution with time of lymphangioma circumscriptum.